Histopathological Effects of Reserpine Treatment Using Fluoxetine and Hordeum vulgare Extract on Some Vital Organs in Rats Depression Model - Wafaa Younis; Koko, Waleed (AlQalam Journal of Medical and Applied Sciences, 2026)
The current study set out to examine the histopathological effects of reserpine (Res) with fluoxetine (Flux) and Hordeum vulgare aqueous extract (HVE) in a rat model with subchronic depression. The tissues of the liver, kidney, testes, and brain were examined histopathologically. Liver histological changes include inflammatory leucocyte infiltration and mild hydropic degradation of the hepatocytes. When compared to a liver portion containing only Res, the liver section including Res, Flux, and HVE demonstrated a higher level of restoration and hepatocyte improvement. Degeneration of renal tubules and interstitial capillary congestion were observed in the kidney treated with Res. Where the kidney received Res., Flux., and HVE, found with normal interstitial tissues, also the Bowman capsules with the glomerulus and renal tubules were normal. The testis that was generated with Res. showed an uneven layer of spermatogonia, necrosis of the lining germinal epithelium, and significant degeneration of seminiferous tubules. The testis, however, is almost under control with normal seminiferous tubules and the entire structure after receiving Res., Flux., and HVE. Rats exposed to Res. exhibited brain abnormalities, including the presence of dead neuronal and non-neuronal cells in the second and third layers of the cortex. Additionally, fluoxetine-exposed individuals exhibited pyramidal cell death and Purkinje cell loss, as well as atrophy, degeneration, necrosis, and inflammation. After receiving Res., Flux., and HVE, the brain displayed a high level of restoration and some indications of recovery, including a regression in the size of the degenerative vacuoles. In conclusion, light microscopic analyses revealed that Fluoxetine showed partial protective effects against reserpine-induced histopathological alterations. on the brain, testis, liver, and kidney. In these tissues, however, HVE and fluoxetine showed improvement.